Late-Medieval Animal Remains in Grave-Like Pits: A Case Study of Rituals in 15th-Century Finland. - Hukantaival, Sonja; Bläuer, Auli; Helamaa, Maija; Uotila, Kari (Medieval Archaeology, 2023)
DURING ARCHAEOLOGICAL EXCAVATIONS at the site of Kärsämäki manor garden in Turku, SW Finland, the team found clusters of oblong pits resembling human graves in an area between the manor and a late-medieval village. No human remains were recovered from these pits; instead, some of them contained bones of domestic animals (cattle, horse and pig). The radiocarbon dates of the animal bones placed them roughly in the 15th century. This paper analyses the Kärsämäki faunal material using a taphonomical and contextual approach. The questions for which answers have been attempted concern the nature of the site and the interpretation of the animal deposits. The results suggest the presence of selected animal parts in certain pit features was a result of deliberate placement. Deposition of animal remains into grave-like pits have been recorded at other late-medieval sites in Finland, but the bones themselves have not been radiocarbon dated. The Kärsämäki site seems to be a location for different types of ritual activities involving animal remains.